Designing a Listening Quiz Through Android-Based Application - Liya Umaroh; Yani Parti Astuti; Egia Rosi Subhiyakto (Universitas PGRI Semarang, 2020)
Since the governmnet proclaimed to WFH (Work From Home) during Covid-19 outbreak, online learning has fully implemented across the entiry universities. Lecturers are forced in technological literacy. Start to prepare all teaching materials, assesments, and evaluation. Therefore designing E-learning is highly worthwhile through collaborative research , between English lecturer and Information Technology lecturers. Prototyping is used for research method. The design process begins with requirements, quick design, built prototype, user evaluation, refining prototype, implement and maintain. Furthermore the main purpose of this research is designing a listening quiz through android based application and it is expected that the application will be used to assess listening class during online learning.